Managerial Ability and Value Creation among Small Businesses in Lagos State - Nigeria - Olajide Okunbanjo; Gabriel Okwuelum (Bina Nusantara University, 2025)
Competitive level of business activities in Lagos State as a commercial hub of Nigeria is high for small businesses. This makes small businesses struggle to penetrate and compete with their counterparts; mid and large businesses with an element of renewal in their business processes. Thus, the study investigated managerial ability and value creation of small businesses in Lagos State. Th study made used of survey research data with purposive sampling to collect data from the small business owners that are registered with SMEDAN using structured questionnaire. The study used simple regression as the statistical tool to report that managerial skills have a positive and significant effect (β=1.174; p=.000) on value creation of small businesses in Lagos metropolis. Managerial roles have a positive and significant effect (β=1.987; p=.000). on value creation. The study concluded that managerial ability helps small businesses operating in Lagos metropolis to create value in order to compete in the markets that are control by mid and large businesses. It was recommended that small business owners/managers should continue to possess the need skills that will enhance their business practices towards creating value for the customers or clients. Also, small business owners/managers should focus more on decisional, informational and interpersonal capacities in order to continue to create values for their businesses